Formulation, implementation, and control of competitive strategy - Pearce, John A. II; Robinson, Richard B. (Homewood, IL : Irwin, 1991)
This text portion provides a readable up-to-date introduction to the management of strategy in the business enterprise.
Rev. ed. of: Formulation and implementation of competitive strategy.
Includes bibliographical footnotes and index.
ucj 16/01/2019
Loans
Keywords: Strategic planning